Elderly Patients with Moderate Chronic Ischemic Mitral Regurgitation: Coronary Artery Bypass Grafting Alone or Concomitant Mitral Annuloplasty? - Ji, Qiang (Cardiol Res Pract, 2019)
BACKGROUND: An increasing number of elderly patients with ischemic mitral regurgitation (IMR) are referred for coronary artery bypass grafting (CABG). However, data about the management of elderly patients with moderate IMR are scanty. This study evaluates the impacts of two surgical approaches (CABG alone or concomitant mitral annuloplasty (MAP)) on in-hospital and midterm outcomes, to attempt to determine an appropriate treatment option for elderly patients with moderate chronic IMR. METHODS: All eligible patients over 65 years of age were included and were entered into either a MAP group (patients undergoing CABG plus MAP, n = 96) or a CABG group (patients receiving CABG alone, n = 104). Baseline and surgical characteristics were analyzed, and in-hospital and midterm outcomes between groups were compared after propensity score-matching (1 : 1). RESULTS: Using propensity score-matching, 82 pairs of patients were successfully established in a 1 : 1 ratio. No significant differences between the two matched groups were found regarding surgical mortality (4.9% vs. 1.2%, p=0.173) and major postoperative morbidity. 150 patients (76 in the MAP group and 74 in the CABG group) received regular follow-up visit with the median duration of 37 months. Compared with the CABG group, the MAP group received a similar overall survival but a better recurrent MR-free survival (stratified log-rank p, 0.492 and < 0.001, respectively). Using Cox regression, the MAP group as compared with the CABG group did not affect midterm survival probability (propensity score-adjusted hazard ratio, 0.854; 95% confidence interval, 0.571–2.729, p=0.630). Additionally, patients in the MAP group had a significantly lower ratio of NYHA class III-IV at the latest follow-up by comparison with patients in the CABG group (19.7% vs. 35.5%, p=0.033). CONCLUSION: Compared with CABG alone, concomitant mitral annuloplasty is associated with improved midterm outcomes (including reduced IMR recurrence and improved cardiac functional class) but shares similar surgical mortality and major postoperative morbidity and may be a promising treatment option for elderly patients with moderate chronic IMR.